Sulcus fluid volume, IL‐6, and Il‐1b concentrations in periodontal and peri‐implant tissues comparing machined and laser‐microtextured collar/abutment surfaces during 12 weeks of healing: A split‐mouth RCT. Issue 1 (16th October 2021) - Guarnieri, Renzo; Miccoli, Gabriele; Reda, Rodolfo; Mazzoni, Alessandro; Di Nardo, Dario; Testarelli, Luca
Abstract: Objectives: To compare gingival tissue healing at surgically manipulated periodontal sites and at sites receiving implants and healing abutments with machined (MS) vs laser‐microtextured (LMS) surface placed with one‐stage protocol. Material and Methods: Twenty‐four non‐smoking patients each received two implants with one‐stage protocol in a split‐mouth design on the same jaw. In each patient, one implant with a MS collar and one immediate healing abutment with a MS, and one implant with a LMS collar and one immediate healing abutment with a LMS were used. Soft tissues healing at surgically manipulated periodontal tissues (T+) and at non‐surgically manipulated periodontal tissues (T‐) at MS implant sites and at LMS implant sites were compared by means of clinical and biochemical parameters at baseline and at 1–2–3–4–6–8 and 12 weeks. Results: PD and BoP mean values were statistically higher in MS than LMS implant sites ( p <0.05). During early healing phase (1–4 weeks), MS and LMS peri‐implant tissues and periodontal tissues at T(+) showed no statistically significant difference in crevicular fluid volume changes ( p >0.05). Between 6 and 12 weeks, compared with T(+), no statistically significant difference in crevicular fluid volume and IL‐6 and IL‐1β concentrations was noted in LMS implant sites ( p >0.05), while statistically significantly higher mean values were noted in MS implant sites ( p <0.05). Conclusions: Compared with T(+) and T(‐), both MS and LMS implant sites presented a higher pro‐inflammatory state in the early phase after surgery (1–4 weeks). At 12 weeks, only MS implant sites kept a higher pro‐inflammatory state, while at LMS implant sites, it becomes similar to T(+) and T(‐).